Students’ Goals, Defectism, Hope, Positive and Negative Evaluation of School - Suzić, Nenad (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
At a huge sample of 1136 students of the eighth and ninth grade of primary school, as well as of the first and second grade of secondary school, the authors separated four components of target orientation of students by factorization: (1) vulnerability, (2) asociality, (3) affiliative motive and (4) efficiency. They applied the instrument Personality test and job satisfactionof Jim Barett (Barrett, 2009), adapted it to the age and needs of this research[1], and then they intersected the separated factors with defeatism, hope as well as positive and negative school valuation. Defeatism and hope were measured by DIN test (Defeatism and hope; Suzic, 2017). Positive and negative valuation of school was recorded by DENS test (Suzic, 2009). All students are from Bosnia and Herzegovina of the age from 13 to 16. Half of the sample included Bosniak students and half of it Serbs. The findings show that there are significant differences between Bosniaks and Serbs in terms of majority of observed variables, but that differences can be attributed to the size of the sample and environment rather than nationality. The students that have higher score, achieve better school results in hope test. Negative valuation of the school is connected with defeatism of students. The authors discovered some significant predictors of negative valuation of school. These are: vulnerability, hope, asociality, defeatism, efficency and affiliative motive. These findings are very significant for pedagogic theory and teaching practice because so far we have not had any research data about the relation of comprised variables.